To answer this item, we express the y in the first equation in terms of the other variables. This is,
y = 7 + z - 2x
Then, substitute the y's in the second and third equation with that of the expression derived in the first equation.
(2) -x - 2(7 + z - 2x) + 4z = -15
Simplifying,
-x - 14 -2z + 4x + 4z = -15
Simplifying further,
3x + 2z = -1
(3) x + 2(7 + z - 2x) - 5x = 17
Simplifying,
x + 14 + 2z - 4x - 5x = 17
Simplifying further,
-3x - 3z = 3
The equations derived are,
3x + 2z = -1
x + z = -1
The values of x and z in the equation are 1 and -2, respectively. To solve for y,
y = 7 + (-2) - 2(1) = 3
ANSWERS: x = 1, y = 3, and z = -2